Endogenizing prospect theory's reference point - Ulrich Schmidt; Horst Zank (Kiel Institute for the World Economy (IfW), 2010)
In previous models of (cumulative) prospect theory reference-dependence of preferences is imposed beforehand and the location of the reference point is exogenously determined. This note provides a foundation of prospect theory, where reference-dependence is derived from preference conditions and a unique reference point arises endogenously.
Keywords: D81; 330; Prospect theory; reference point; diminishing sensitivity; loss aversion